Greensburg envisioned - Anterola, Jeremy; Becker, Andrew; Blackwell, Jessica; Bonser, Skyler; Capps, Scott; Curry, Collin; Henley, Jacob; Jacobson, Melody; Jaquez-Herrera, Clemente; Kroen, Kevin; LaMartina, Josh; Rader, Julianne; et al. (Kansas State University, 2009)
May 4, 2007, a tornado ripped across Kiowa County, Kansas, leveling ninety-five percent of the town of Greensburg and leaving the rest of the town severely damaged. Shortly after the tornado, a 12-week process of meetings and discussions by teams of local, state, and federal officials, business owners, civic groups, and hundreds of citizens resulted in “Long-Term Community Recovery Plan: Greensburg + Kiowa County, Kansas ” (LTCRP), which expresses the Greensburg/Kiowa County community’s vision for recovery. In the LTCRP, the inhabitants of Greensburg expressed a strong will to strategize the reconstruction of a new, sustainable rural town. In October 2007, KSU College of Architecture, Planning and Design professors coordinated fourth year landscape architecture and fifth year architecture students to begin addressing the design needs of Greensburg. The aim was for students to create sustainable design conceptualizations for projects specifically listed in the LTCRP. Students were to communicate the following to the general public: some basic sustainable design practices, and, how these practices could manifest in a design concept for Greensburg. The student projects would then serve as a catalyst for conversation as the town considers their reconstruction efforts. From the beginning, architecture and landscape architecture students were instructed to work together on design proposals that encompassed aspects of ecological sensitivity, resource efficiency and resident health and well-being. It was soon acknowledged that, for the reconstruction of a small town, sustainability has broader implications than the generally accepted definition of reduced environmental impact, conscientious resource use, and the preservation of human well-being. Ensuring the viability of the community - its economy, institutions, and infrastructure - was of vital importance. Communicating these needs, potential design solutions and design logic to the general public was an architecture-landscape architecture student effort. In December 2007, the design concepts were given to the citizens of Greensburg. A public gallery exhibited the work, digital files of all student project images and text were placed on the internet, and paper copies of all work were given to the City.
Keywords: Community vision; Sustainability; Student communication; Greensburg, Kansas; Landscape architecture; Architecture; Architecture